REACTIONS OF FELDSPAR SURFACES WITH AQUEOUS SOLUTIONS - Chardon E.S.; Livens F.R.; Vaughan D.J. (My University, 2006)
Reactions involving feldspars are of great importance in the environment, influencing geochemical cycles in many ways. Dissolution of feldspars has been widely studied in the laboratory, with attempts being made to reproduce and understand the processes of "weathering" as seen in the environment. It has long been recognised that weathering of feldspars involves the attachment and detachment of atoms at the surface of the mineral. A wide range of factors influences the reactions involved, from the composition of the feldspar to the nature of the solution, but it is generally accepted that weathering leads to the presence of a leached layer, with a composition different from both the bulk mineral and the fluid. The aim of this paper is to review recent work carried out on feldspars, focusing particularly on developing an understanding of the leached layer using both spectroscopic methods (including Secondary Ion Mass Spectroscopy and X-ray Photoelectron Spectroscopy), and microscopic imaging techniques (including Atomic Force Microscopy and Scanning Electron Microscopy) to follow changes at the mineral/solution interface. Contrasting models of surface evolution are discussed. © 2006 Elsevier B.V. All rights reserved.
Keywords: DISSOLUTION-REPRECIPITATION; FELDSPAR; LEACHED LAYER; STOICHIOMETRY; WEATHERING